Ghosts of Havana : Judd Ryker #3 - Moss, Todd (New York : G.P. Putnam's Sons, 2016)
"A timely international thriller by the former deputy assistant secretary of state and bestselling author"--.
"A timely international thriller by the former deputy assistant secretary of state and bestselling author"--
Keywords: Government investigators -- Fiction; Conspiracies -- Fiction; FICTION / Suspense; FICTION / Political; FICTION / Espionage; United States -- Foreign relations -- Cuba -- Fiction; Cuba -- Foreign relations -- United States -- Fiction; Suspense fiction; Mystery fiction; Political fiction